IL-6 activated integrated BATF/IRF4 functions in lymphocytes are T-bet-independent and reversed by subcutaneous immunotherapy - Mousset, Stephanie; Koch, Sonja; Mousset, Stephanie; Graser, Anna; Reppert, Sarah; Uebel, Caroline; Reinhardt, Cornelia; Zimmermann, Theodor; Rieker, Ralf; Lehr, Hans A.; Finotto, Susetta (Scientific Reports, 2013)
IL-6 plays a central role in supporting pathological TH2 and TH17 cell development and inhibiting the protective T regulatory cells in allergic asthma. TH17 cells have been demonstrated to regulate allergic asthma in general and T-bet-deficiency-induced asthma in particular. Here we found an inverse correlation between T-bet and Il-6 mRNA expression in asthmatic children. Moreover, experimental subcutaneous immunotherapy (SIT) in T-bet((-/-)) mice inhibited IL-6, IL-21R and lung TH17 cells in a setting of asthma. Finally, local delivery of an anti-IL-6R antibody in T-bet((-/-)) mice resulted in the resolution of this allergic trait. Noteworthy, BATF, crucial for the immunoglobulin-class-switch and TH2,TH17 development, was found down-regulated in the lungs of T-bet((-/-)) mice after SIT and after treatment with anti-IL-6R antibody, indicating a critical role of IL-6 in controlling BATF/IRF4 integrated functions in TH2, TH17 cells and B cells also in a T-bet independent fashion in allergic asthma.